L-shaped association of thiamine intake and risk for peripheral artery disease in US adults: a cross-sectional study - Dong, Zhiyong; Wang, Qingyun (Frontiers in Nutrition, 2024)
Background The relationship between thiamine intake and risk for peripheral artery disease (PAD) is unknown. We aimed to clarify the role of thiamine intake on risk for PAD and the implications of this relationship. The secondary objective of this study is to explore the potential non-linear dose–response relationship between exposure to thiamine intake and outcome risk for PAD. Methods We conducted a cross-sectional study involving 6,112 participants with US adults from the National Health and Nutrition Examination Survey (1999–2004). Logistic regression and restricted cubic spline were utilized to substantiate the research objectives. Results The overall prevalence of risk for PAD was 7.9, 51% in males and 49% in females. After multivariable adjustment, lower thiamine intake was significantly and nonlinearly associated with higher risks of PAD among participants. Furthermore, we discovered L-shaped associations (p = 0.082) between thiamine intake and the risk of PAD, with an inflection point at 0.66 mg/day. Accordingly, in the threshold effect analysis, there was an inverse association between dietary thiamine intake and the risk in participants with dietary thiamine intake <0.65 mg/day. Compared to participants with thiamine intake below the inflection points, those with higher levels had a 31% lower risk for PAD (OR, 0.69; 95% CI: 0.51, 0.95). Further subgroup analysis showed no significant interactions between the subgroups (all p values for interaction were > 0.05). Conclusion A non-linear association was revealed, showing that low and high levels of thiamine intake were associated with an increased the risk of peripheral artery disease in American adults. The inflection point at 0.66 mg/day and lower risk of PAD at 0.65–1.13mg/day of dietary thiamine intake may represent intervention targets for lowering the risk of PAD. The findings of this study require further validation and confirmation.